علم اللغة الجغرافي بين حداثة المصطلح وأصوله لدى العرب (Geographical Linguistic Study between Modern Terminology and its Origin among Arab People) - (Abdel Aziz b. Hamid al-Hamid), عبد العزيز بن حميد الح (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2014)
ملخص البحث: يتناول هذا البحث علماً جديداً في اصطلاحه وتكوينه، وهو (علم اللغة الجغرافي)، وهو تسمية حديثة لعلم يشترك في بحوثه علمان هما: علم اللغة، وعلم الجغرافيا، يأتي علم اللغة وعلم الجغرافيا علمين منفصلين في ميدانين متباعدين، فعلم اللغة يتعلق بلغة الإنسان وما يتصل به من فروع وقضايا، وعلم الجغرافيا يتعلق بالبلدان والمناطق وما يتصل بها من مسائل بعيدة عن اللغة، ولا يشكّ المطلع على التراث العربيّ أنه كان "عند العرب بذور علم اللغة الجغرافي الذي يدرس العلاقة بين الظاهرة اللغوية ومجال انتشارها، وإن لم تكن على نحو علمي صارم، وتبدو في أخذهم رواية اللغة عن الأعراب في البوادي ووضع الحدود بين اللهجات وقبائلها. سأحاول في الصفحات الآتية أن أكشف عن حداثة علم اللغة الجغرافيّ لدى الغربيّين وهو من علم اللغة التطبيقي، مع الكشف عن أعمال العرب التي تدخل تحته، سواء أكانوا لغويّين أم جغرافيّين. ومحاولتي هذه هي لإبراز تكامل الجهود وإن كانت بلغاتٍ مختلفة وحضارات متعدّدة. وفي موضوعنا هذا يتجلّى النضج الحديث على أيدي الغربيّين لهذا العلم (علم اللغة الجغرافي). الكلمات المفتاحية: علم اللغة- الأطلس اللغوي- المعاصرون- جهود القدامى- المقدسي. Abstract: This research studies new knowledge both in its term and composure. It is (Geographical Linguistic study). It is a new name for a study which contains two different knowledge in its works; Linguistics and Geography. These disciplines come from two different fields of knowledge. Linguistics deals with Human languages and entire what relate to it from branches and issues, while Geography studies what relate to towns, regions and all matters that have links with it, which are so far from Language. Whoever has access to Arab Heritage will not maintain no doubt that source of Geo- Linguistics existed in Arab Legacy, which takes care of relationship between Linguistics phenomenon and its expansion; it may not be capable of been based on organized scientific way as it is in Western study. The vast example for Geo- Linguistics in Arab Heritage can be traced to reporting of language from Arab Bedouins and erecting boundaries among the dialects and tribes in the work of early Arabia Grammarians. This paper will explore in the next pages, recent Geo- Linguistics study in the West, which was laid down under Applied Linguistics and bring out some Arab works that have links with this knowledge either from Linguistics or Geographers. My effort is to exhibit integrated endeavors from different languages and multi civilizations. In this topic, current discovery from Westerners will be exhibit for this knowledge Geo- Linguistics. Keywords: Linguistics- Linguistic Atlas- Contemporary- Ancient efforts- Sanctified. Abstrak: Kajian ini mengupas satu istilah yang menggabungkan di antara dua disiplin kajian: linguistic dan geografi; kedua-duanya adalah cabangan disiplin ilmu yang berbeza di dalam dua bidang yang berbeza. Linguistik adalah kajian bahasa manusia dan isu-isu yang berkaitan dengannya manakala geografi pula adalah kajian berkenaan tempat-tempat dan isu-sisu yang berkaitan dengannya. Tidak dinafikan bagi mereka yang melakukan kajian yang berkenaan bahawa bangsa Arab telah mempunyai benih-benih cabang disiplin kajian ini yang melihat hubungkait di antara fenomena bahasa dan juga kawasan ia tersebar. Ia mungkin tidak sejelas kaedah ilmiah moden, namun usaha mereka merekodkan ungkapan bahasa daripada penutur Badwi dan melukis sempadan dialek kabilah-kabilah di sesuatu tempat merupakan landasan cabang disiplin ini. Artikel ini akan menghuraikan perkembangan cabang disiplin ilmu ini di kalangan sarjana Barat dan bagaimanakah usaha-usaha pengkaji bahasa Arab lampau dan para sarjana geografinya turut boleh dianggap sebagai usaha awal cabang kajian moden tentang bahasa ini. Ussaha ini ialah untuk menunjukkan susur galur perkembangan sesuatu cabang ilmu itu yang datang dari latar sejarah , tamadun serta bahasa yang berbeza-beza dan bagaimana ia telah mencapai tahap kematangannya yang turut di sumbangkan oleh sarjana-sarjana moden Barat. Kata kunci: Linguistik– Atlas Bahasa– Sarjana Kontemporer– Usaha Sarjana lampau– Al–Maqdisiy.